Labour and employment in a globalising world. Autonomy, collectives and political dilemmas (Frankfurt am Main, 2010)
"This collection of essays provides new insight into the complex realities of labour and employment market globalisation. The pluridisciplinary and multi-faced understanding of globalisation is based upon ground research in ten countries from South to North. Its contextualisation of globalising labour and employment market, perceived as process, constitutes the originality of the book. Globalisation is understood through a single process of both standardisation and differentiation, which also underscores its political agenda. The globalising process incorporates trends of convergent and somewhat undifferentiated Southern and Northern situations in labour and employment. Strong political perspectives thereby emerge to help understand changes in current capitalism and question the longstanding North to South paradigm. As labour and employment markets standardise and differentiate, what other problematical threads can be pulled to strengthen the hypothesis that trends converge within a single globalising process? The comparative concepts and tools proposed in this volume help to answer these queries. "